Exploring Representation of 19th-Century French Society in the Novel La Bête Humaine: A Sociological Literary Approach - Novriska, Emmanuela Cristomarry; Sunahrowi, Sunahrowi (Journal of Language and Literature Studies, 2026)
Literary works serve not only as a means of aesthetic expression, but also represent the dynamics of social life. Émile Zola’s novel La Bête Humaine represents the dynamics of 19th-century French society, characterized by industrialization, moral crisis, social inequality, and complex power relations. In this context, Georg Simmel’s theory of social interaction is relevant for understanding how relationships between characters shape behavior within social structures, and enables an analysis of the interrelationship between patterns of interaction, social structure, and power dynamics in society. The aim of this study is to analyze various forms of social interaction in Émile Zola’s novel La Bête Humaine and reveal how these interactions reflect the social conditions of 19th-century French society. The method used is descriptive qualitative with a sociological approach to literature based on Georg Simmel’s theory of social interaction. The material object is the novel La Bête Humaine, while the formal objects include concepts of social interaction such as dyads, triads, strangers, conflict, and secrets. Data in the form of narrative quotations and dialogue were collected through literature studies and close reading techniques, then analyzed using manifest and latent content analysis techniques to interpret the social meanings contained. The findings indicate that social interaction within the novel not only shapes relationships between characters but also reflects the social structures that influence behavior and character. Dyads, triads, and the stranger reveal relationships between characters that develop into mechanisms trigger destructive actions, whilst conflict and secrets expose tensions within power relations, social inequality, and moral crises in 19th-century French society. This study contributes to the field of literary sociology by emphasizing that social interaction within a text is not merely interpersonal, but is linked to broader social structures.